Relevansi Ketersediaan Koleksi Perpustakaan Dengan Kebutuhan Informasi Siswa Kelas XII SMAN 1 Peranap Kabupaten Indragiri Hulu Riau - Asning, Prayumi Wikanti; Nelisa, Malta (JURNAL PENDIDIKAN ROKANIA, 2023)
The background of this research is for the information needs of class XII students of SMAN 1 Peranap which must be met by the library, the lack of collections available at SMAN 1 Peranap, the lack of fulfillment of information needs by the library of SMAN 1 Peranap. The research uses quantitative research methods with descriptive research methods. Data analysis was carried out using descriptive methods by compiling and grouping data. Furthermore, the data is arranged according to the group of aspects studied. The research instrument used by the researcher was observation and questionnaires. The results showed that the availability of collections in the library of SMAN 1 Peranap was still quite relevant. Most of the users stated that the library of SMAN 1 Peranap needed to add or improve the collection or library language to suit the information needs of users or class XII students. The facilities and infrastructure provided by the library of SMAN 1 Peranap have supported the teaching and learning process activities.